Clinimetric Testing in Mexican Elders: Associations with Age, Gender, and Place of Residence - Tavano-Colaizzi, Lorena; Arroyo, Pedro; Loria, Alvar; Pérez-Lizaur, Ana Bertha; Pérez-Zepeda, Mario Ulises (Frontiers in Medicine, 2014)
Aim. To evaluate the ability of five clinimetric instruments to discriminate between subjects >60 years of age living at home versus those living in a residency. Methods. Trained nutritionists applied five instruments (Cognition/ Depression/ Functionality/ Nutrition/ Appetite) to 285 subjects with majorities of women (64%), aged <80y (61%) and home residents (54%). Results. Multivariable regression models were generated for each instrument using age, gender and residency as independent variables. Age was associated with worsening scores in the five instruments whereas residency showed association in three instruments, and gender in two. Score-age regressions by place of residency showed differences suggesting that Mundet residents had increasingly worse scores with increasing age, than home dwellers for Cognition, Depression and Nutrition. Also, living at home prevented the worsening of Depression with increasing age. In contrast, Functionality and Appetite deteriorated at a similar rate for home and Mundet residents suggesting an inhability of these two instruments to dicriminate between settings. Score-age regressions by gender suggested males have less cognitive problems at 60 and 80 years of age but not at 100, and better appetite than women at all ages. Conclusions. Increasing age proved to be associated to worsening scores in the five instruments but only three were able to detect differences according to setting. An interesting observation was that living at home appeared to prevent the Depression increase with increasing age seen in Mundet residents.